Development of Digital Social Studies Teaching Materials in The Era of Pandemic Emergency Learning - Khoiron, Muhammad; Harmanto, Harmanto; Kasdi, Aminuddin; Wardani, Agnia Rizki (The Indonesian Journal of Social Studies, 2021)
This research aims to explain the development of digital IPS teaching materials that can be used to improve critical thinking skills during a pandemic. With a focus on, 1) How is(X) the application of digital teaching materials in learning, (2) How do(X) students respond to teaching materials, and (3) How are(X) the effectiveness of teaching materials. The Data were collected by observation, interviews, and tests. The research location was located at one of the junior high schools in the city of Surabaya. The effectiveness test used Mann Whitney in the control class (not using the developed teaching materials) and the experiment (using the developed teaching materials). The results of the study show; 1) Social studies learning is more optimally carried out asynchronously, (2) The students response to teaching materials is positive, and (3) the results of the difference test between the control and experimental classes show a difference. In the control class, the critical thinking ability tends to be constant and the answers to the test results are homogeneous and textbook, while in the experimental class it shows an increase in critical thinking skills and the answers to the test results vary according to the environment of each students.